Reaction Mechanisms of Non-hydrolytic Atomic Layer Deposition of Al2O3with a Series of Alcohol Oxidants - Seo, Seunggi; Woo, Whang Je; Lee, Yujin; Yoon, Hwi; Kim, Miso; Oh, Il Kwon; Chung, Seung Min; Kim, Hyungjun; Shong, Bonggeun (Journal of Physical Chemistry C, 2021)
Atomic layer deposition (ALD) of Al2O3 using trimethylaluminum (TMA) and H2O is the most widely and deeply studied ALD process owing to the superior properties of the deposited Al2O3 thin films and usability of TMA and H2O. However, H2O can cause undesirable substrate oxidation during ALD. While previous studies have shown that alcohol oxidants can be used to deposit Al2O3 thin films with less substrate oxidation, the reaction mechanism of ALD Al2O3 with alcohol oxidants has not been elucidated yet. In this study, the reaction mechanism of ALD of Al2O3 thin films using various alcohol oxidants was systematically investigated by computational and experimental methods. Various possible reaction pathways are considered for the oxidation of Al-CH3 with methanol (MeOH), ethanol (EtOH), and propanol (n-PrOH). It is found that the feasible reaction mechanism for removal of the surface-adsorbed alkoxy group is autocatalytic liberation of alkene through β-hydrogen transfer. ALD processes were developed using the alcohol oxidants. Our process using EtOH showed a growth rate of 0.96 Å/cycle and a moderate level of carbon impurities (2.6%). In addition, we investigated the properties of ALD-deposited Al2O3 thin films with alcohol oxidants, which indicated superior electrical properties and decreased formation of interfacial oxide on the Si substrate.
Keywords: Carbon impurities; Experimental methods; Hydrogen transfer; Interfacial oxides; Reaction mechanism; Reaction pathways; Substrate oxidation; Trimethylaluminum